Sierra Madre lounge, circa 1989 (1989)
Students seating in the lounge area of Sierra Madre. An educational poster regarding alcohol and alcoholism is in display on the wall behind them, with typical behaviors for Comfortable Abstainer, Usual Abstainer, Light Drinker, Frequent User, Occasional Abuser, and Alcoholic listed.